How do you solve (3x )/ (x+1) = 12 / (x-1)?

1 Answer
Apr 25, 2018

the answer is x=(5+sqrt(41))/(2), (5-sqrt(41))/(2)

Explanation:

first you have to cross multiply and you get: 12x+12=3x^2-3x and now move all the terms to one side to make it equal to zero. 3x^2-15x-12=0 and you can take out 3 from all numbers so: 3(x^2-5x-4)=0 since you can't factor the parenthesis equation, you have to use the quadratic formula which is: (-bsqrt(b^2-4ac))/(2a) and put in the respectful numbers in:-(-15)sqrt(4(3)(-12))/(2(3)) and now solve to get your answer